Effect of rare-earth elements on microstructure and mechanical properties of in-situ Fe-TiB2 composites. (December 2021) - Zhang, Lin; Huang, Minghao; Zhang, Daoqi; Wang, Engang
Abstract: By integrating stiff and light TiB2 particles into an iron matrix, the Fe-TiB2 composite provides a viable approach for lightweight structural material design. The Fe-TiB2 composites are fabricated by melting and casting with TiB2 particles produced in-situ by a pseudo-binary eutectic reaction during solidification. However, this results in coarsening of TiB2 particles and thus degrades the mechanical properties of the fabricated composites. In this study, Sm, Y, Gd, Nd, Ce, and La were added to hypereutectic Fe-TiB2 composites (Fe–10.35% Ti–18 at% B). The effects of the addition of different rare-earth (RE) elements on the microstructure and mechanical properties of the composites were studied. Alloying the composites with Sm, Y, Gd, Nd resulted in the coarsening of TiB2 primary particles in Fe-TiB2 composites while lowering their number density; however, it also reduced the eutectic spacing and size of the α-Fe grains. This reduced the average interparticle spacing, leading to marginally increased tensile strength and hardness. Furthermore, the addition of Ce and La significantly refined the TiB2 primary particles and scattered them into a more dispersive distribution while the eutectic spacing and size of the α-Fe grains decreased. Alloying with La, in particular, primarily reduced the interparticle spacing, resulting in a significant strengthening of mechanical characteristics. The La-added specimen reached an ultimate tensile strength (UTS) of up to 778.2 MPa and a hardness of up to 3.96 GPa, respectively 15.1% and 32.9% higher than that of the non-RE specimen.